Pine Briquetting- An Endeavour for Green Fuel - Pandey, J. C.; Gangwar, Prachi; Kumar, Naresh; Grewal, Neena (Indian Forester, 2014)
The project introduced pine briquetting as a pioneer venture to meet the objective of reducing the drudgery of hill women and also the incidences of forest fires. Pine briquetting is an income generating activity where the user groups sell the briquettes in the village and in the nearby market. 260 Pine needle briquette making machines were installed in 283 revenue villages and 8020 households were provided smokeless stoves for domestic purposes. On an average, in a span of four years, 6526.2 Qt pine briquettes were produced by 3809 group members of which 1513.6 Qt briquettes were marketed and the beneficiaries earned a sum or ` 15.97 Lac from this activity during the project period. Overall 76.81 per cent of briquettes are used domestically while only 23.19 per cent was marketed. The shifting of rural household from fuel wood to pine briquettes has reduced the fuel wood needs by 1.1 MT per year per household using it. An ideal alternative fuel, pine briquetting is also a good livelihood option for the beneficiaries because a wide range of its commercial usage exists.